Tourette syndrome - Brill, Marlene Targ. (Brookfield, Conn. : Twenty-First Century Books, 2002)
Examines the tic disorder known as Tourette syndrome, its symptoms and manifestations, how it can be controlled and treated, and, through case studies, what it is like to live with Tourette's.
Includes bibliographical references (p. 93-94) and index.
Keywords: Tourette syndrome -- Juvenile literature; Tourette syndrome -- Case studies -- Juvenile literature; Tourette syndrome in children -- Juvenile literature; Tourette syndrome; Tic disorders